Relationship Between Resting-State Functional Magnetic Resonance Imaging and Different Time in Target Glucose Range in Elderly Patients with Type 2 Diabetes Mellitus - Yang P; Liu S; Li L (Diabetes, Metabolic Syndrome and Obesity)
Ping Yang,1 Shudong Liu,1 Liyan Li2 1Department of Endocrinology, Shandong Rongjun General Hospital, Jinan, 250013, People’s Republic of China; 2Department of Endocrinology, First People’s Hospital of Jinan, Jinan, 250011, People’s Republic of ChinaCorrespondence: Liyan Li, Department of Endocrinology, First People’s Hospital of Jinan, No. 132 Daming Lake Road, Lixia District, Jinan, Shandong, 250011, People’s Republic of China, Email shashuang2513@163.comPurpose: This study aimed to investigate the relationship between the resting-state functional magnetic resonance imaging (rs-fMRI) indices and time in target glucose range (TIR) in elderly type 2 diabetes mellitus (T2DM) patients.Methods: Ninety-eight elderly T2DM patients were divided into the low-TIR (TIR≤ 70%) and high-TIR groups (TIR> 70%). The two groups’ clinical variables, neuropsychological scale scores, and rs-fMRI scan data were collected. The rs-fMRI including low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). The changes and the interrelationships of these indicators were analyzed in the two groups.Results: Compared with the high-TIR group, disease duration, blood urea nitrogen, urine microalbumin were significantly greater (P< 0.01) diastolic blood pressure and albumin were significantly lower (P< 0.05) in the low TIR group. In the low-TIR group, the Cerebelum_Crus2_R ReHo value was significantly increased (voxel p< 0.001, cluster p< 0.05), the Frontal_Inf_Orb_R ReHo value was significantly decreased, the Cerebelum_Crus2_R and Frontal_Mid_L ALFF values were significantly increased, the Temporal_Sup_L and Precuneus_R ALFF values were significantly decreased; the Lingual_L fALFF value was significantly decreased. Increased ReHo values in differential brain regions between the low and high TIR groups were positively correlated with HbA1c (P = 0.042), and decreased ReHo values were significantly negatively correlated with HbA1c (P=0.026) and urine microalbumin (P=0.005) levels. Decreased ALFF values in differential brain regions were significantly negatively correlated with the basal C-peptide level (p=0.007) and significantly positively correlated with the basal Mini-Mental State Examination (MMSE) score (p = 0.048).Conclusion: ReHO, ALFF, and fALFF value differences were present between the low and high TIR groups. Elderly T2DM patients in the low-TIR group were more susceptible to impaired brain function, which presented mainly as abnormal reduction in and activation of functional activity in some temporal lobes, frontal lobes, and occipital lobes in the resting state, and more significant when glycemic control is poorer.Keywords: type 2 diabetes mellitus, time in range, resting-state functional magnetic resonance imaging, low-frequency fluctuation, fractional low-frequency fluctuation, regional homogeneity